A Model for University-Based International Plastic Surgery Collaboration Builds Local Sustainability. Issue 4 (April 2015) - Rockwell, William Tyler; Agbenorku, Pius; Olson, Joshua; Hoyte-Williams, Paa Ekow; Agarwal, Jayant P.; Rockwell, William Bradford
Abstract : Abstract: This article aimed to assess the sustainability from collaboration between international plastic surgery consultants and a hospital of a developing country in the promotion and delivery of quality health care to the local population. Humanitarian medical missions have evolved in structure and volume during the last 40 years. Medical mission trips were initially designed to treat local populations and help decrease the burden of disease. A limited number of the local population benefited from the mission. Some mission trips evolved from not only treating the local population but also teaching local physicians. These trips produced some local sustainability. Host physicians carried on a broader range of care after the mission trip had departed. Further evolution of these medical trips involves not only care and teaching but also involvement of host medical students and residents. Regularly scheduled Internet-based consultations and educational conferences expand the educational opportunities. The sustainability of medical trips based on this model is maximized. This process still has limitations: a limited number of the local population are treated during the in-country 1-week visits, Internet reliability may limit the transmission or quality of conferences, and differences in hospital resource availability may limit transference of US techniques to other hospitals.